Institutional Reform for Innovation and Entrepreneurship An Agenda for Europe - Elert, Niklas; Henrekson, Magnus; Stenkula, Mikael (SpringerBriefs in Economics,, 2017)
This book is open access under a CC BY 4.0 license.